Sea surface wind field by X-band terrasar-X and tandem-X - Lehner, Susanne; Li, Xiao Ming; Ren, Yong Zheng; He, Ming Xia (European Space Agency (Special Publication) ESA SP, 2013)
In the present study, we present the newly developed Geophysical Model Function (GMF), denoted XMOD2, to retrieve the sea surface wind field from X-band TerraSAR-X/Tandem-X (TS-X/TD-X) data. In contrary to the previous XMOD1, XMOD2 is based on a nonlinear GMF, and moreover it also depicts the difference between upwind and downwind of the sea surface backscatter. By exploiting 371 collocations, the retrieved TS-X/TD-X sea surface wind speed by XMOD2 agrees well with in situ buoy measurements with a bias of 0.39 m/s, an RMSE of 1.52 m/s and a scatter index (SI) of 16.1%. To evaluate the sea surface wind field retrieved from X-band SAR, we conducted a joint campaign in the South China Sea in August, 2011. Examples of sea surface wind field retrieved from the TS-X/TD-X data acquired in the campaign are shown for demonstration.
CRIS-Team Scopus Importer:2024-03-18